(3Yjhf GdCNHGQ (B((3aj GdCOH(B)s ((3CSjhW (B((3UYjO eUQ(B)s)
(3ChdgG (B:s
(3bGd(B: (3CfTOfG GdNWjH CHhHcQ CMeO Hf Ydj Hf KGHJ GdMGaX GdHZOGOj dfaSg(B: (3eG dNdb Edi GdNdhO SHjd cja jchf GdJShja hGdJYdjd s
(3BNQgG (B:s
(3adFf XaQJ HeTab aj hOg Ch eTabI BNQ eG JjSQ JNQjLg hGdMeO ddg haQZ ef fSNI eNqQLg s
(3HgG fXGe GdJYbjHIs
(3aj cTa GdXfhf (B1183/2 (3heG HYOgG hEjVGM Gdecfhf (B133/2 (3CcKQ ef cJGH HgPG GdGSes
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs